A biblioterapia como proposta de um programa para portadores de deficiência visual na seção braille da Biblioteca Pública Arthur Vianna - LOBO, Laís Machado (2017)
Treats Biliotherapy as a proposl to the Braille section of the Arthur Vianna public library, the applied bibliotherapeutic methods and how the librarian could act like a Bibliotherapist. Reports the visual impairment and the importance of Braille on the reading and writing these disabled individuals. The general objective of this paper is to propose to the Braille section the Bibliotherapy technique, another reading attraction and the visually impaired’s psychosocial improvement, turning them into participant and useful individuals to the community. The used methodology descriptive and exploratory, quantitative-qualitative, study with bibliographical research with a source of authors considered relevant in the area of librarianship and bibliotherapy in order to unveil and propose the importance of reading as a therapy for all, specifically the visually impaired. An interview was conducted with two servers in the Braille section of the Arthur Vianna Library and a blind user, with the purpose of knowing the space, services provided, frequency and proposing improvements to the library.